The Effect of STAD Application on Student Learning Outcomes in English Class V ICP English at Elementary School: Pengaruh Penerapan STAD Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Inggris Kelas V ICP di SD - Essa Mulia Rifanti; Ruli Astuti (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims the problems experienced by the fifth grade ICP students of SD Muhammadiyah 3 Ikrom regarding the relatively low learning outcomes of English. This is due to the lack of motivation during learning and the boredom felt by students. Researchers chose the STAD learning model because it can keep up with the times, namely by using online learning media in the form of the Zoom application. The researcher did a Breakout Zoom to divide the group. This research uses experimental quantitative research methods. The T-test on the SPSS program was also carried out to analyze whether there was an influence and how much influence the student learning outcomes had after the implementation of the Student Teams Achievement Division learning model. The results of the study indicate that there is a significant influence from the application of the STAD learning model. There was a significant increase in the average score from Pre-Test to Post-Test. Meanwhile, the magnitude of the effect of the application of the STAD learning model can be seen in the results of the T-test analysis with T-count > T-table, which means H0 is rejected and Ha is accepted.